2011
DOI: 10.1089/lap.2011.0141
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Adrenalectomy in Children: A Multicenter Experience

Abstract: The laparoscopic approach can be applied for adrenalectomy in children for a wide variety of conditions regardless of age with a 90% chance of completing the operation without conversion. The risk for significant blood loss or complications is low, and it should be considered the preferred approach for the majority of adrenal lesions in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 13 publications
0
23
0
4
Order By: Relevance
“…International Pediatric Endosurgery Group guidelines [5] states that LA is technically feasible in children and can be performed in selected patients for benign and malignant tumors. Indeed, in large reviews [1,6], safety of LA has been demonstrated with a low conversion rate. In 2004, Porpiglia et al [7] reported that LA was a feasible option for ACC, if the principles of oncological surgery are respected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…International Pediatric Endosurgery Group guidelines [5] states that LA is technically feasible in children and can be performed in selected patients for benign and malignant tumors. Indeed, in large reviews [1,6], safety of LA has been demonstrated with a low conversion rate. In 2004, Porpiglia et al [7] reported that LA was a feasible option for ACC, if the principles of oncological surgery are respected.…”
Section: Discussionmentioning
confidence: 99%
“…Adrenalectomy by minimal invasive surgery is used worldwide since the 1990s but experience in children remains limited. However, in a large multicentric study [1], it has been showed that LA can be used regardless of age and should be considered as the preferred approach for the majority of adrenal lesions in children.…”
Section: Dear Editorsmentioning
confidence: 99%
“…Porém, foi observado que este sistema apresentava uma falha na separação prognóstica entre os estágios II e III (65). Posteriormente, o grupo europeu (ENSAT) propôs um novo sistema de estadiamento (Tabela 2) que tem sido recomendado para a padronização na estratificação prognóstica de pacientes adultos.…”
Section: Estadiamento Tumoralunclassified
“…Pacientes em que o tumor foi diagnosticado e tratado ainda no estágio I apresentam cerca de 82% de sobrevida após cinco anos de segmento, enquanto em pacientes diagnosticados já em estágio IV, a sobrevida em cinco anos é de cerca de 18% (65).…”
Section: Prognóstico E Opções De Tratamentounclassified
See 1 more Smart Citation